ANALISIS ISI PERUT IKAN NILA (OREOCHROMIS NILOTICUS) DI KERAMBA JARING APUNG (KJA) DANAU BATUR, BALI - Ni Komang Lina Tetri Saraswati; Gede Iwan Setiabudi; Hamdanul Fain (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to identify feed composition and analyze the Frequency of Occurrence (FO) of both natural and artificial feed in the digestive tract of Nile tilapia. The research employed a quantitative descr iptive approach with purposive sampling techniques, in which 40 fish (150–300 g) were collected from four geographical locations (North, South, East, and West). The digestive tract contents were preserved using 4% formalin and identified using a binocular microscope (10×–40× magnification). The results revealed a broad dietary spectrum consisting of 20 taxa, dominated by Bacillariophyceae, Chlorophyceae, Zygnematophyceae, Cyanobacteria, and Zooplankton. Four taxa exhibit ted an absolute FO value of 100%: Nitzschia sp., Chlorella sp., Microcy stis sp., and Brachionus sp., while pellet fragments showed a relatively low FO value of only 10%. The presence of periphytic organisms (Epithe mia sp., Navicula sp.) and benthic mites (Hydrachnidia sp.) indicates active grazing behavior of fish on the floating net cage structures. The consistent presence of Microcystis sp. acts as a bioindicator of eutrophic ation in Danau Batur. Concludes that Nile tilapia cultured in floating net cages still significantly utilize natural feed resources, thereby providing opportunities to improve the efficiency of artificial feeding management.